PROJECT MANAGEMENT, NETWORKS AND VALUE CREATION IN UNIVERSITY SPIN OFFS - Corsi, Christian; Di Berardino, Daniela (European Scientific Journal, ESJ, 2013)
The paper analyses the operational characteristics of university spin offs and the features of their networks in some territorial clusters. In particular, it observes the system of intangible resources the enterprise manages, then the structure and the impact on the business performances of the applied project management models as well as the features of the network of relations the managers created. The sample consists of 134 enterprises, out of them 105 are located in five clusters of academic spin offs, which have been selected taking into account the territorial density and the most prolific universities in Italy, in improving the of the research by starting up a business. The research questions are expressed in the following way: in a specific business field, what role does the university spin off play within the network of relations with external stakeholders? What intangible resources are essential to success? How does the project management contribute to the efficiency of the business action? The data useful to the empirical analysis are obtained from questionnaires and document sources drawn from national data bases, corporate, ministerial and university sites. Social network and correlation analyses have been carried out on the sample; empirical evidences lead to observations which are useful to understand excellences/critical situations of spin offs in specific territorial clusters, with useful implications for the management of research processes.